DIOGENITES AS ASTEROIDAL CUMULATES: INSIGHTS FROM ORTHOPYROXENE TRACE ELEMENT CHEMISTRY - Fowler G.W.; Shearer C.K.; Papike J.J.; Layne G.D. (My University, 1995)
Eucrite, howardite, and diogenite members of the achondrite meteorites are considered by many to be genetically related. Therefore, each provides a piece of the puzzle for reconstructing magmatic processes on the eucrite parent body (EPB). The interpretation of the magmatic history of the diogenites (orthopyroxenites) is compromised to a great extent because the magmatic major element signature of orthopyroxene has been reset and some minor elements such as Al have been compromised by coupled substitution mechanisms. As a further test of the models for the origin of diogenites, we have analyzed a suite of twenty-one diogenites (~160 individual analyses) for minor and trace elements using ion microprobe techniques.The concentrations of incompatible elements are low in the orthopyroxenes analyzed, while their variability in the orthopyroxenes is both extensive and consistent. The range of averages in Yb varies by a factor of 16 from Ellemeet to LEW 88679. Over this suite of diogenites, Zr varies by a factor of 117 and Y varies by a factor of 151. This variability exceeds the range noted by previous INAA studies of orthopyroxene separates. These incompatible trace elements exhibit a strong positive correlation with Ti. The consistent incompatible element variability among diogenites, limited textural evidence for subsolidus exsolution modification, and the expected slower diffusion rates of the REE, Ti, and Y relative to Fe-Mg indicate that the trace elements in the diogenitic orthopyroxene may reliably preserve the magmatic history of the diogenites.Based on the incompatible trace element systematics of Y and Yb, over 90% crystallization is necessary to explain the variation in concentrations from Peckelsheim (most depleted) to LEW 88679 (most enriched) assuming constant D's. Over 70% crystallization of orthopyroxene is required if DY and DYb increase by a factor of three over the same suite of diogenites. Based on terrestrial analogs, it appears highly unlikely that a single basaltic magma will produce such a mono-mineralic orthopyroxene cumulate horizon with 70-90% crystallization of the parental melt. Two models that potentially explain this extensive incompatible element variability are: (1) the melts from which the diogenites formed are normative orthopyroxene enriched and normative plagioclase depleted or; (2) the suite of diogenites represent multiple basaltic melts with distinctly different incompatible element enrichments.Melt compositions that were back-calculated from the orthopyroxene data indicate that the diogenites crystallized from melts that had a wider range in incompatible elements than that exhibited by the main group eucrites. If the assumptions made in the calculation of these melts compositions are correct, this may be interpreted to mean that either many of the diogenites are not fractional crystallization products of eucritic melts or that the eucritic melts that were parental to the incompatible element enriched diogenites have not yet been sampled.